COMPARATIVE ANALYSIS OF FINANCIAL PERFORMANCE AT PT. KIMIA FARMA TBK AND PT. SIDO MUNCUL TBK IN THE PERIOD BEFORE AND DURING THE COVID 19 PANDEMIC - Rini Martiwi; Nyoman Suardita; Aan Rahman; Instianti Elyana (Jurnal Akuntansi Dan Bisnis Indonesia (JABISI), 2023)
This study compares the financial performance of PT Kimia Farma, Tbk, and PT Sido Muncul, Tbk in the pre-pandemic period and during the COVID-19 pandemic. The type of data used is secondary data obtained from the Indonesia Stock Exchange in the form of the financial reports of PT Kimia Farma Tbk and PT Sido Muncul Tbk before the Covid-19 pandemic (2018-2019) as a reflection of conditions before the COVID-19 pandemic and the 2020-2021 financial reports as a reflection of conditions during the COVID-19 pandemic. The data analysis tool used SPSS version 22 and the Wilcoxon Sign Test, a non-parametric test used to analyze data in two related groups, including cases before and after where the same object was observed under two conditions. The results of the research show the performance of PT. Kimia Farma Tbk and PT. Sido Muncul Tbk, there is a significant difference in the performance of PT. Sido Muncul Tbk is better than PT. Kimia Farma Tbk. both before the pandemic and during the Covid 19 pandemic, where the performance of PT. Sido Muncul Tbk is better than PT. Kimia Farma Tbk, both before the pandemic and during the Covid 19 pandemic.